Pedogenesis Dan Klasifikasi Tanah Yang Berkembang Dari Dua Formasi Geologi Dan Umur Bahan Erupsi Gunung Tangkuban Perahu - Mahfud Arifin; Rina Devnita; Ridha Hudaya; Apong Sandrawati; Daud Siliwangi Saribun; Rachmat Harryanto; Ganjar Herdiansyah (Soilrens, 2017)
The efforts to utilize the agricultural land need a proper understanding of the soil characteristics. The soil characteristics themselves are influenced by the factors that regulate and control the soil forming and pedogenesis processes. The main soil forming factors in this study was the different ages and composition of parent materials from the eruption of Mt. Tangkuban Parahu in West Java. This research was done to comprehend the pedogenesis and to figure out the soil classifications that developed in two geological formations (Qyd and Qvu) and two ages of eruption (Holocene and Pleistocene) of Mt. Tangkuban Parahu. The study was conducted in Ciater, Subang Regency and Jatinangor, Sumedang Regency in West Java Province. The study consisted of four stages: preparation, field survey and soil sampling, laboratory analysis and presenting the report. The results showed that Pedon of Jatinangor consisted of three different stratifications of ages. The clay mineralogical composition was dominated by kaolinite, whereas mineralogical composition of the sandy fractions (heavy fractions) was augite-hypersthene. Pedon of Ciater also consists of three different stratifications of age. The clay mineralogical composition was dominated by allophane, while mineralogical compositions of the sandy fractions (heavy fractions) were green amphibole-hypersthene in the overlying horizons and amphibole-augite in the underlying horizons. The stage of soil formation on both pedon were cambic or viril. The soil classification according to Soil Taxonomy were Acrudoxic Durudands, medial over loamy-skeletal, isohyperthermic in Ciater Pedon and Fluventic Eutrudepts, fine, kaolinitic, isohyperthermic in Jatinangor Pedon.Key words: slow sand filter, activated carbon, silica sand, sand, gravel, zeolite